Antique expanding bed at Straumen Farm in Norway - Campbell, Sandy (2024)
Most of the beds at the Straumen Farm in Tromsø Municipality, Norway, were of this design. The headboard and foot board are the size of a single bed, but one of the side-rails pulls out to expand the bed to a double bed. This design expands the sleeping surface at the same level, while most trundle beds or truckle beds are two separate sleeping surfaces, one stored below the other. This bed is made of stained wood, with turned horizontal spindles at each end, and turned wood decorations on the tops of the bed posts, painted black. The short legs are also turned wood and painted black. The bed is shown partly opened.